Pengaruh Pajak, Mekanisme Bonus dan Tunneling Incentive terhadap Transfer Pricing - Rizanti, Della Feby; Karlina, Lilis (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to analyze the influence of taxes, bonus mechanisms and tunneling incentives on transfer pricing in industrial sector companies listed on the IDX for the 2018-2022 period. The total research population was 63 samples taken from 12 industrial sector companies over a 5 year period. industrial companies listed on the IDX using a purposive sampling method. Research data was analyzed using panel data regression analysis. This research obtained using Eviews 12 shows that the simultaneous variables of tax, bonus mechanism, and tunneling incentive have a significant effect on transfer pricing. Partially, taxes have a significant effect on transfer pricing, bonus mechanisms have a significant effect on transfer pricing, and Tunneling Incentive has a significant effect on transfer pricing.